Anatomic Double-Bundle Medial Patellofemoral Ligament Reconstruction with Autologous Semitendinosus: Aperture Fixation Both at the Femur and the Patella - Vasso, Michele; Corona, Katia; Toro, Giuseppe; Rossini, Marco; Schiavone Panni, Alfredo (Joints, 2017)
Medial patellofemoral ligament (MPFL) represents the main restraint against lateral patellar displacement. The MPFL insertion at the patella is up to 30 mm wide and is located along the upper half of the medial patellar rim. The femoral insertion of the MPFL is approximately 10 mm distal to the apex of the adductor tubercle and 16 mm proximal to the medial epicondyle. Since most of the patients suffer from MPFL rupture just after the first patellar dislocation, MPFL reconstruction results necessarily in all cases of chronic objective patellar instability to reestablish the primary passive patellofemoral stabilizer. Over time, different techniques of MPFL reconstruction have been proposed with promising results in terms of patient satisfaction and redislocation rate. However, each of these techniques may present peculiar problems and/or complications. An anatomic double-bundle MPFL reconstruction through an aperture fixation both at the femur and at the patella is here presented. The anatomic double-bundle MPFL reconstruction could allow recreating the fan-shape and biomechanics of original MPFL, whereas aperture fixation could provide a strong and safe fixation without risk of loosening or slackening of the graft.
Keywords: medial patellofemoral ligament; reconstruction; double-bundle; aperture fixation; semitendinosus